Effect of Location on Tracheal Intubation Safety in Cardiac Disease—Are Cardiac ICUs Safer?. Issue 3 (March 2018) - Gradidge, Eleanor A.; Bakar, Adnan; Tellez, David; Ruppe, Michael; Tallent, Sarah; Bird, Geoffrey; Lavin, Natasha; Lee, Anthony; Adu-Darko, Michelle; Bain, Jesse; Biagas, Katherine; Branca, Aline; et al.
Abstract : Objectives: Evaluate differences in tracheal intubation–associated events and process variances (i.e., multiple intubation attempts and oxygen desaturation) between pediatric cardiac ICUs and noncardiac PICUs in children with underlying cardiac disease. Design: Retrospective cohort study using a multicenter tracheal intubation quality improvement database (National Emergency Airway Registry for Children). Setting: Thirty-six PICUs (five cardiac ICUs, 31 noncardiac ICUs) from July 2012 to March 2016. Patients: Children with medical or surgical cardiac disease who underwent intubation in an ICU. Interventions: None. Measurements and Main Results: Our primary outcome was the rate of any adverse tracheal intubation–associated event. Secondary outcomes were severe tracheal intubation–associated events, multiple tracheal intubation attempt rates, and oxygen desaturation. There were 1, 502 tracheal intubations in children with underlying cardiac disease (751 in cardiac ICUs, 751 in noncardiac ICUs) reported. Cardiac ICUs and noncardiac ICUs had similar proportions of patients with surgical cardiac disease. Patients undergoing intubation in cardiac ICUs were younger (median age, 1 mo [interquartile range, 0–6 mo]) compared with noncardiac ICUs (median 3 mo [interquartile range, 1–11 mo]; p < 0.001). Tracheal intubation–associated event rates were not different between cardiac ICUs and noncardiac ICUs (16% vs 19%; adjusted odds ratio, 0.74; 95% CI, 0.54–1.02; p = 0.069). However, in a sensitivity analysis comparing cardiac ICUs with mixed ICUs (i.e., ICUs caring for children with either general pediatric or cardiac diseases), cardiac ICUs had decreased odds of adverse events (adjusted odds ratio, 0.71; 95% CI, 0.52–0.97; p = 0.033). Rates of severe tracheal intubation–associated events and multiple attempts were similar. Desaturations occurred more often during intubation in cardiac ICUs (adjusted odds ratio, 1.61; 95% CI, 1.04–1.15; p = 0.002). Conclusions: In children with underlying cardiac disease, rates of adverse tracheal intubation–associated events were not lower in cardiac ICUs as compared to noncardiac ICUs, even after adjusting for differences in patient characteristics and care models. Abstract : Supplemental Digital Content is available in the text.